NEW TRENDS IN CONSUMPTION ON THE COFFEE MARKET (Polityki Europejskie, Finanse i Marketing)
The aim of the article is to present trends in consumption, which currently affect or will affect the behaviour of coffee consumers in the next 2-5 years. The article is written in the form of theoretical considerations supported by an analysis of source materials. It presents the main megatrends, consumer trends and product trends observed on the coffee market. It also describes relations between the aforementioned phenomena and consumer behaviour. The analysis of the collected data made it possible to conclude that the main trends determining consumer behaviour are naturalness and sustainability, health and nutrition, multisensory experience, convenience, digitalisation and individualisation. In order to meet these trends, producers and sellers of coffee will also want to gain an influence on the choices and preferences of coffee consumers by supporting and developing such product trends as: craft coffee time, the ice age is coming, ready to drink coffee, co-branding to dial up indulgence, convenient formats go premium, the rise of super coffee or the world of smart vending machines.